Gambaran Kejadian Komplikasi Nyeri Kepala Pada Pasien Pasca Anestesi Spinal di Ruang Kebidanan Rumah Sakit Umum Tgk Chik Ditiro Sigli Kabupaten Pidie Aceh - Mustafa Mustafa; Roro Lintang Suryani; Ita Apriliyani (Universitas Harapan Bangsa Purwokerto, 2023)
Post Dural Puncture Headache (PDPH) is the most common complication that occurs in spinal anesthesia techniques resulting from a tear in the dura mater which causes a leak in the Cerebrospinal Liquor (LCS). This study aims to describe the incidence of complications of headache in post-spinal anesthesia patients. This research method is a quantitative descriptive method with a cross-sectional study design. The population and sample of this study were all post-sectio caesarea patients with spinal anesthesia in the last 1 month of January 2022, namely 46 people using the total sampling technique. Data is taken directly from the subject as a source of information under study, namely the results of observations. The results showed that the majority of PDPH incidents were 18 respondents (39.1%) aged 30-39 years, most of them experienced PDPH with a mild pain scale of 12 respondents (37.5%), most of the respondents who experienced PDPH had BMI with the normal category as many as 16 respondents (34.8%), the majority of respondents who experienced PDPH with a quinckie needle size of 26 were 18 respondents (39.1%). This study concluded that most of the respondents who experienced PDPH were aged 30-39 years with normal BMI and a quinckie needle size of 26 at Tgk Chik Ditiro Sigli General Hospital, Pidie Aceh District.